Curvature of the diffraction cone of proton-proton elastic scattering at high energies in maximal Pomeron and Odderon model - Lengyel, O.; Bence, N.; Szanyi, I. (Problems of Atomic Science and Technology, 2023)
The values of the slope B(s,t) and curvature parameter C(s,t) have been calculated within the framework of the maximal Pomeron and Odderon approach in the wide s- and low t-range with the allowance made for the diffraction cone shape. The absolute values of the averaged curvature parameter <C(s,t)> is predicted to be decreasing depending on s and change of sign at asymptotically large energies far from achievable ones. Нахил B(s,t) та параметр кривизни C(s,t) розраховані у рамках моделі максимального Померона та Оддерона у широкому діапазоні s і при малих t з урахуванням форми дифракційного конуса. Передбачається, що абсолютне значення усередненого параметра кривизни <C(s,t)> спадає залежно від s і змінює знак при асимптотично високих енергіях, далеких від досяжних.